Aeromonas spp. in Freshwater Bodies: Antimicrobial Resistance and Biofilm Assembly - Maria Nascimento; Joao Rodrigues; Rui Matias; Luisa Jordao (MDPI AG, 2024)
Aeromonas spp. are environmental bacteria able to infect animals and humans. Here, we aim to evaluate the role of biofilms in Aeromonas persistence in freshwater. Aeromonas were isolated from water and biofilm samples and identified by Vitek-MS and 16S rRNA sequencing. Antibiotic susceptibility profiles were determined according to EUCAST, and a crystal violet assay was used to assess biofilm assembly. MTT and the enumeration of colony-forming units were used to evaluate biofilm and planktonic Aeromonas susceptibility to chlorination, respectively. Identification at the species level was challenging, suggesting the need to improve the used methodologies. Five different Aeromonas species (A. salmonicida, A. hydrophila, A. media, A. popoffii and A. veronii) were identified from water, and one species was identified from biofilms (A. veronii). A. veronnii and A. salmonicida presented resistance to different antibiotics, whith the highest resistance rate observed for A. salmonicida (multiple antibiotic resistance index of 0.25). Of the 21 isolates, 11 were biofilm producers, and 10 of them were strong biofilm producers (SBPs). The SBPs presented increased tolerance to chlorine disinfection when compared with their planktonic counterparts. In order to elucidate the mechanisms underlying biofilm tolerance to chlorine and support the importance of preventing biofilm assembly in water reservoirs, further research is required.